Testing the Generalizability of the Event Process Model of Family Violence With an Incarcerated Sample - Stairmand, Meg (International journal of offender therapy and comparative criminology, 2021)
The event process model of family violence (FVEPM) presents a descriptive theory of a family violence (FV) event from the perpetrator’s perspective. Developed in a community setting, the FVEPM is comprised of four interrelated sections and describes three pathways to FV perpetration (Pathway 1: Conflict escalation, Pathway 2: Automated violence, and Pathway 3: Compliance). This study further developed the FVEPM by testing the generalizability of the model and its pathways with an incarcerated sample of eight men with extensive histories of violent and other offending. Event narratives were gathered during individual semi-structured interviews, and were systematically analyzed using grounded theory methods. Overall, findings suggest that the FVEPM and its pathways can accommodate an incarcerated sample. However, several inconsistencies were found: Event narratives were better represented by splitting Pathway 1 into two sub-types, and no event narratives were assigned to Pathway 3. Implications for FV theories and treatment are discussed.